Re-discovering Evolution: A National Literature between Tautology and Renewal - Kazbek K. Sultanov (Studia Litterarum)
This article attempts to analyze the evolution of literary thinking as a key concept in the systematic study of a national literature. Methodological requirements to describe literary dynamics as completely as possible prompt a rediscovery of the evolutionary principle, which can be characterized both as an open system of meaning-making and a dialectic of the constant and the changeable contingent on the temporal factor. The focus of this paper is on transitional states, borderline phenomena, semantic recoding, the release of new possibilities of a national literature, and explosive points of literary development when artistic discovery is perceived as a breakthrough challenging inertial normativity. The article reconstructs concepts of A. Bergson, G. Gukovsky, and especially Yu. Tynyanov who developed the notion of “literature as a system” in its natural relation to literary evolution.